Contribution of phosphocreatine and aerobic metabolism to energy supply during repeated sprint exercise - Bogdanis, G.C., Nevill, M.E., Boobis, L.H., Lakomy, H.K.A. (Journal of Applied Physiology, 1996)
This study examined the contribution of phosphocreatine (PCr) and aerobic metabolism during repeated bouts of sprint exercise. Eight male subjects performed two cycle ergometer sprints separated by 4 min of recovery during two separate main trials. Sprint 1 lasted 30 s during both main trials, whereas sprint 2 lasted either 10 or 30 s. Muscle biopsies were obtained at rest, immediately after the first 30-s sprint, after 3.8 min of recovery, and after the second 10-and 30-s sprints. At the end of sprint 1, PCr was 16.9 ± 1.4% of the resting value, and muscle pH dropped to 6.69 ± 0.02. After 3.8 min of recovery, muscle pH remained unchanged (6.80 ± 0.03), but PCr was resynthesized to 78.7 ± 3.3% of the resting value. PCr during sprint 2 was almost completely utilized in the first 10 s and remained unchanged thereafter. High correlations were found between the percentage of PCr resynthesis and the percentage recovery of power output and pedaling speed during the initial 10 s of sprint 2 (r = 0.84, P < 0.05 and r = 0.91, P < 0.01). The anaerobic ATP turnover, as calculated from changes in ATP, PCr, and lactate, was 235 ± 9 mmol/kg dry muscle during the first sprint but was decreased to 139 ± 7 mmol/kg dry muscle during the second 30-s sprint, mainly as a result of a  45% decrease in glycolysis. Despite this  41% reduction in anaerobic energy, the total work done during the second 30-s sprint was reduced by only  18%. This mismatch between anaerobic energy release and power output during sprint 2 was partly compensated for by an increased contribution of aerobic metabolism, as calculated from the increase in oxygen uptake during sprint 2 (2.68 ± 0.10 vs. 3.17 ± 0.13 l/min; sprint 1 vs. sprint 2; P < 0.01). These data suggest that aerobic metabolism provides a significant part ( 49%) of the energy during the second sprint, whereas PCr availability is important for high power output during the initial 10 s.